Stem cell transplant: An experience from eastern India - A Mukhopadhyay; P Gupta; J Basak; A Chakraborty; D Bhattacharyya; S Mukhopadhyay; U K Roy (Indian Journal of Medical and Paediatric Oncology)
Background: Hematopoietic stem cell transplant using human leukocyte antigen (HLA)-matched sibling or unrelated bone marrow, or related or unrelated cord blood has been performed successfully to treat patients with different types of hematological malignancies, genetic disorders and hereditary immune deficiencies. Since 1983, stem cell transplantation has been carried out in different institutes of India. But, till then, no transplantation was performed in eastern India. Materials and Methods: Our present study is reporting for the first time stem cell transplantation in eastern India. From August 2000 to June 2011 (with a 3-year gap for up-gradation), we have performed a total of 22 transplants. Thirteen patients (M:F:9:4) with indications of aplastic anemia, thalassaemia, acute myeloid leukemia and chronic myeloid leukemia underwent allogenic transplant, whereas autologous transplant was performed for nine patients (M:F:2:1) of multiple myeloma, Hodgkin′s and non-Hodgkin′s lymphoma and neuroblastoma. The median age of the patients was 19.6 years, with a range of 5 years 8 months to 52 years. Fourteen patients received myeloablative conditioning regime whereas eight patients received immunosuppressive and less myeloablative protocol. Sources of stem cells in case of allogenic transplant are bone marrow and related or unrelated umbilical cord blood and in case of autologous transplant, these are peripheral blood stem cells or self-bone marrow. Standard prophylactic medication was followed prior to transplants. Results: A disease-free survival of 68.18% and overall survival of 86.3% were seen at the median follow-up period of 4.6 years. Common post-transplant complications were mucositis, infection, venoocclusive disease, graft versus host disease, hemorrhagic cystitis, etc. Conclusion: The use of cord blood as a source of stem cells has been proved inferior as compared with the bone marrow stem cell source in cases of thalassaemia in our institute and thus is not recommended for thalassaemia. But, it has been proved to be a very useful and effective stem cell source (both related and unrelated cord blood) in cases of aplastic anemia and other immunological disorders.